Natural Products As Preservatives - ANUPAMA SINGH; PRAMOD KUMAR SHARMA; GARIMA GARG (International Journal of Pharma and Bio Sciences, 2010)
Natural preservatives are the chemical agents derived from plants, animals, microbes and their metabolites that prevent the decomposition of products by any means. The mode of action of these natural preservatives is inhibition of microbial growth, oxidation and certain enzymatic reactions occurring in the foodstuffs. This review limelight various naturally derived constituents such as essential oils, flavonoids, phenolic compound, microbial metabolites and antimicrobial constituents of other foods that possesses the preserving action. These natural preservatives are gaining importance in recent years as they have little or no harmful effects. Currently pharmaceutical and food industries are emphasizing more on this scenario. This review details the methods of bio preservation to evaluate their efficacy in extending the shelf life and improving the microbial safety of pharmaceutical and food products.